Whatever happened to the Brethren? a survey of local churches in 1998-99 - Brown, Graham (Carlisle, UK Paternoster/Partnership, 2003)
Includes bibliographical references and diagrams.
Brethren writer
Keywords: Brethren movement -- United Kingdom -- history, late 20th century